Synthesis and characterization of magnesium sulphate based composite solid electrolytes / Noorhaslin Che Su - Noorhaslin , Che Su (2016)

(untitled)
In this study, magnesium-based composite solid electrolytes systems were successfully prepared via a sol-gel method. Magnesium sulphate and magnesium nitrate hexahydrate salts were used as starting materials and act as host matrices. Meanwhile, aluminium oxide and magnesium oxide were used as dispersoids in preparing the composites. The prepared composite solid electrolytes were characterized using X-ray diffraction, differential scanning calorimetry, scanning electron microscopy, energy dispersive X-ray and Fourier transform infrared spectroscopy. Impedance measurement was used to study the conductivity and the ionic transportation mechanism. The X-ray diffraction analysis showed anhydrous magnesium sulphate had undergone solid-solid transition phase to ?-MgSO4 phase which occurred during sintering process at 900 ?C. All of the prepared composite samples had undergone recrystallization process before changed into amorphous structure. This has further confirmed by differential scanning calorimetry analysis and scanning electron microscopy images. Addition of second phase into the composite systems has lowered the melting and decomposition temperatures of the composites. Fourier transform infrared spectroscopy showed that complexation had occurred between magnesium salts (magnesium sulphate and magnesium nitrate) with the metal oxide (aluminum oxide and magnesium oxide). This has been proved by disordered structure of the composite samples after addition of the dispersoid. Moreover, scanning electron microscopy displayed the images of cross - sectional pellets of the three systems. It shows that ?-MgSO4 was well spread over the alumina surfaces which had contributed to good interface between host and the disperosid. Besides that, with addition of second phase (dispersoid) into the composite system, the formation of amorphous phase of MgSO4 had occurred and the MgSO4:Al2O3 interface increased the conductivity of the system via mobility of Mg2+ cations along the Al2O3 surface. In addition, the formation of MgO from the composite systems had formed a better inter-grain contact hence show enhancement in conductivity. The prepared composite samples for the first and second system had achieved the highest conductivity of 10-7 S cm-1 at room temperature. However, with the addition of MgO as disperosid in the third system, the conductivity was enhanced to 10-6 S cm-1 at room temperature. This enhancement showed that MgO plays an important role in conducting magnesium ions. Besides that, addition of magnesium nitrate into the composite system has contributed to the formation of new MgO in the composite systems. It was observed that, the highest conductivity achieved for the first and second system at room temperature was 1.6 ×10-7 S cm-1 and 6.4×10-7 S cm-1 respectively. This was due to the presence of magnesium nitrate in the second system that enhanced the conductivity. In addition, all the composite solid electrolyte systems were thermally activated at high temperature. The association between Mg2+ cations from the amorphous phase of MgSO4 and the new MgO phase has resulted in the formation of MgO: Mg2+ interfaces which facilitated the mobility of Mg2+ cations thus enhancing the conductivity of composite systems. Overall, this study have been focusing in developing Mg2+ ion conducting in composite solid electrolyte that will applicable in magnesium secondary batteries.